Hypermethylation of the OPRM1 and ALDH2 promoter regions in Chinese Han males with alcohol use disorder in Yunnan Province. (2nd November 2021) - Liu, Linlin; Yang, Xiaopei; Zhao, Fei; Gao, Changqing; Zhang, Ning; Bao, Jianjun; Li, Kuan; Zhang, Xulan; Lu, Xiaoxiao; Ruan, Ye; Zhong, Shurong
ABSTRACT: Background: Alcohol use disorder (AUD) is one of the most serious public health problems worldwide. The OPRM1 and ALDH2 genes are important factors in the reward and alcohol metabolism pathways, and their DNA methylation patterns are closely related to AUD and are population-specific. Chinese Han people are the most populous ethnic group in the world, and this group experiences severe AUD. No epigenetic study on OPRM1 and ALDH2 has been performed in Chinese Han patients with AUD. Objectives: To investigate whether methylation patterns of OPRM1 and ALDH2 are associated with susceptibility to AUD in Chinese Han males. Methods: DNA methylation of the OPRM1 and ALDH2 promoters was studied in Chinese Han males with AUD in Yunnan Province (N = 50 controls, N = 90 individuals with AUD) using the bisulfite pyrosequencing method. Results: In the AUD group, compared with the control group, OPRM1 was hypermethylated(p < .01) but there was no significant difference in the methylation level of ALDH2 (p > .05). 9 CpG sites of OPRM1 (p < .05) and 2 CpG sites of ALDH2 (p > .01) were hypermethylated. Smoking promoted AUD-mediated hypermethylation of OPRM1, in which 3 CpG sites showed significant hypermethylation ( p < .01). Age had no significant effect on the DNA methylation levels of these two genes. Conclusions: Our study demonstrates that DNA hypermethylation of the OPRM1 and ALDH2 promoter regions is associated with an increased risk of AUD, which may help to explain the pathogenesis and progression of AUD.